A prospective study on the efficacy of mobilization of autologous peripheral stem cells in pediatric oncohematology patients. Issue 7 (3rd October 2012) - Cesaro, Simone; Tintori, Veronica; Nesi, Francesca; Schiavello, Elisabetta; Calore, Elisabetta; Dallorso, Sandro; Migliavacca, Maddalena; Capolsini, Ilaria; Desantis, Raffaella; Caselli, Desirèe; Fagioli, Franca; Luksch, Roberto; et al.
<x xml:space="preserve">Abstract</x> Background Peripheral blood stem cells (PBSCs) are the preferred source in autologous transplantation. We assessed prospectively the efficacy of mobilization in pediatric patients and risk factors associated with its failure. Study Design and Methods Patients, aged 0 to 17 years, needing a first collection of PBSCs for autologous stem cell transplantation were eligible. The study period was from July 2008 to September 2010. A blood peak of fewer than 20 × 106 CD34+ cells/L was used as the cutoff to define a poor mobilizer. Results A total of 145 patients, 57% male (82) and 43% female (63), with a median age of 7 years, affected by solid tumor, 79% (114), and acute leukemia or lymphoma, 21% (31), were enrolled. Granulocyte–colony‐stimulating factor used was filgrastim in 69%, lenograstim in 26%, and pegfilgrastim in 5% of patients. A total of 83% (121) of patients mobilized successfully, the median CD34+ count being 120 × 106/L (range, 23 × 106‐1840 × 106/L). A single leukapheresis procedure was sufficient to achieve the target CD34+ cell dose in 82% (99/121) of patients. Among 24 poor mobilizer patients, 15 underwent a second mobilizing course and nine required a marrow harvest. Factors associated with poor mobilization were metastatic disease and relapse. Among 99 patients who underwent autologous stem cell transplantation, the median times to neutrophil and platelet engraftment and of hospitalization were longer by 2, 12, and 6 days in poor versus good mobilizer group. Conclusions In pediatric patients undergoing a first mobilization, the incidence of poor mobilization was 17%. Failure of mobilization resulted in an increase in health costs and a longer hospitalization for those who underwent autologous stem cell transplantation.